Bearing Yhwh's name at Sinai: a reexamination of the name command of the Decalogue - Imes, Carmen Joy (Bulletin for Biblical Research Supplement Series, 2023)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- List of Figures -- List of Tables -- Foreword -- Acknowledgments -- Abbreviations -- 1. Introduction -- Scope and Need for Research -- Historical and Theological Presuppositions -- Method and Aims -- 2. A History of the Interpretation of the Name Command -- Interpretive Options for the Name Command -- The Name Command as an Elliptical Expression -- The Name Command as a Nonelliptical Expression -- 3. A Reexamination of the Name Command: Lexico-Historical Considerations -- שׁם -- נשׂא -- שׁוא -- נקה -- Conclusion -- Excursus: Psalm 24:4 and Psalm 139:20 in Light of the Name Command -- 4. A Reexamination of the Name Command in the Context of the Decalogue -- The Character of the Decalogue -- The Literary Context of the Decalogue -- The Decalogue as Context for the Name Command -- Conclusion: The Decalogue and the Name Command -- 5. Bearing YHWH's Name at Sinai -- Conceptual Metaphor in Biblical Literature -- Conceptual Metaphor at Sinai -- The Concept of Name Bearing at Sinai -- The Occasion of Bearing YHWH's Name -- Appendix: Semantic Overlap between נשׂא and λαμβάνω -- Bibliography -- Indexes -- Index of Authors -- Index of Scripture.